2001
DOI: 10.1128/cdli.8.1.174-177.2001
|View full text |Cite
|
Sign up to set email alerts
|

Immunodiagnosis of Human Fascioliasis by an Enzyme-Linked Immunosorbent Assay (ELISA) and a Micro-ELISA

Abstract: Enzyme-linked immunosorbent assay (ELISA) and micro-ELISA were evaluated for their ability to detect anti-Fasciola hepatica antibodies in humans by using excretory-secretory antigen. The sensitivity of each method was 100%, but the specificity was 100% for ELISA and 97% for micro-ELISA. The micro-ELISA could be used as a screening assay and ELISA could be used as a confirmatory method for the serodiagnosis of human fascioliasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 18 publications
(10 reference statements)
1
44
0
3
Order By: Relevance
“…Several ELISA techniques have been described for the serodiagnosis of fascioliasis, and most rely on excretory-secretory products (11,15) or recombinant proteases (11,34) that are the major components of ESPs. In the present study, we demonstrated that a cytosolic ferritin-like protein (FhFtn-1) and a tegument-associated protein (FhTP16.5) are also excellent antigens for the serodiagnosis of chronic fascioliasis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several ELISA techniques have been described for the serodiagnosis of fascioliasis, and most rely on excretory-secretory products (11,15) or recombinant proteases (11,34) that are the major components of ESPs. In the present study, we demonstrated that a cytosolic ferritin-like protein (FhFtn-1) and a tegument-associated protein (FhTP16.5) are also excellent antigens for the serodiagnosis of chronic fascioliasis.…”
Section: Discussionmentioning
confidence: 99%
“…The antigens traditionally used in serological tests are crude extracts or excretory-secretory products (ESPs) of F. hepatica (11,15,16). Several F. hepatica purified antigens (17,18) and recombinant antigens have been employed to enhance the specificity of diagnostic assays (11,19,20).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…FAST-ELISA has a sensitivity rate of 95%, although the exact specificity has not been determined. 10,11 Triclabendazole has been shown to be very effective against fasciola hepatica infections. The drug is administered at a dose of 10 mg/kg for 1 or 2 days, and it is well-tolerated.…”
Section: Discussionmentioning
confidence: 99%